CADANGAN ZILLMER STATUS HIDUP GABUNGAN DENGAN ASUMSI BALDUCCI - Rizky Meica Utami; Hasriati '; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses Zillmer’s reserve in joined endowment life insurance for joint life status. Zillmer’s reserve is a reserve calculation of modified premium using prospective reserve and the size of Zillmer’s rate. This calculation is carried out by determined single premium, annual premium, and life annuity in advance based on Balducci’s assumption.